Kaitan Sarapan Pagi, Menu Makanan, Semangat Belajar dan Biaya dengan Prestasi Belajar (Kasus Mahasiswa Matematika dan Biologi FKIP Universitas Islam Riau) - Sandra, Meutia (Jurnal Pendidikan Biologi, 2017)
This study aims to see the relationship between breakfast, food menu, the spirit of learning and the cost of learning achievement. Breakfast with a menu of foods with adequate nutrition is a source of energy and serves to improve the strength and activity of learning and together with the spirit of learning affect the learning achievement. Breakfast is also associated with the cost, cost savings in the menu and nutrition and breakfast routines will affect the learning achievement. Respondents of this research are FKIP students of Islamic University of Riau in math class as much 132 people and biology class as much 83 people. The study was led by a closed questionnaire. The analysis is done by descriptive correlation and inferential statistic by using binary logistic regression. Some findings obtained that there is a link between breakfast, food menu, the spirit of learning and the cost of learning achievement. Using a 10 percent confidence level, a relatively high probability of achievement, first is cost with probability: 0.815, breakfast: 0.758 and learning spirit: 0.733.